How Italian Newspapers Narrate Climate Change. The Role of Media Representations in the Cultivation of Sustainable Collective Imaginary - Ferrucci, Martina; Petersen, Lars Kjerulf (European Journal of Sustainable Development, 2018)
Global warming represents one of the most important societal challenges of our time, but it is often inaccessible to direct human experience. On the contrary, it is largely constituted in the public mind from media narrations. Indeed, media have the power to catch people’s attention and to create collective imaginaries on that issue. For this reason, understanding the way in which media represent climate change can be a strategic starting point in the comprehension of sustainable collective imagination. In the European scenario, Italy symbolizes an interesting case study, not only due to the challenges of sustainable management that this country has to face, but also because, according to Eurobarometer surveys, Italians seem being not particularly concerned about climate change mitigation. Consequently, and considering the impressive development of the Internet, our research is aimed to identify the typology of climate change representation provided by the two most important Italian online newspapers and the role this representations have had on people’s sustainable concerns and narrations (through interview analysis). Our findings allow us to define similarities between media narrations and interviewees’ stories and to understand how important media representations are in raising sustainable awareness among the audiences. Keywords: Sustainability, climate change, media representation, media influence, Italy